Clade classification of monolignol biosynthesis gene family members reveals target genes to decrease lignin in Lolium perenne. (13th March 2015) - van Parijs, F. R. D.; Ruttink, T.; Boerjan, W.; Haesaert, G.; Byrne, S. L.; Asp, T.; Roldán‐Ruiz, I.; Muylle, H.; Hause, B.
Abstract In monocots, lignin content has a strong impact on the digestibility of the cell wall fraction. Engineering lignin biosynthesis requires a profound knowledge of the role of paralogues in the multigene families that constitute the monolignol biosynthesis pathway. We applied a bioinformatics approach for genome‐wide identification of candidate genes in Lolium perenne that are likely to be involved in the biosynthesis of monolignols. More specifically, we performed functional subtyping of phylogenetic clades in four multigene families: 4CL, COMT, CAD and CCR. Essential residues were considered for functional clade delineation within these families. This classification was complemented with previously published experimental evidence on gene expression, gene function and enzymatic activity in closely related crops and model species. This allowed us to assign functions to novel identified L. perenne genes, and to assess functional redundancy among paralogues. We found that two 4CL paralogues, two COMT paralogues, three CCR paralogues and one CAD gene are prime targets for genetic studies to engineer developmentally regulated lignin in this species. Based on the delineation of sequence conservation between paralogues and a first analysis of allelic diversity, we discuss possibilities to further study the roles of these paralogues in lignin biosynthesis, including expression analysis, reverse genetics and forward genetics, such as association mapping. We propose criteria to prioritise paralogues within multigene families and certain SNPs within these genes for developing genotyping assays or increasing power in association mapping studies. Although L. perenne was the target of the analyses presented here, this functional subtyping of phylogenetic clades represents a valuable tool for studies investigating monolignol biosynthesis genes in other monocot species.